Transwestyci (?) w "Thesmoforiach" Arystofanesa - Borowski, Yvonne (Collectanea Philologica, 2011)
The article discusses the question of transvestism in the Thesmophoriazusae of Aristophanes. To provide a useful theoretical backdrop, the author begins with an analysis of the definition of cross-dressing as a complex socio-behavioural phenomenon. Next follows an examination of the four examples of male characters dressing up in female clothing in the analyzed comedy. These are the cases of Agathon, Cleisthenes, Mnesilochus and Euripides. The aim of the investigation is to point out the purposes of employing cross-dressing in the drama as well as to distinct the genuine transvestites among the comic dramatis personae.